Perancangan dan Pembuatan Sistem Informasi Administrasi pada Balai Kesehatan Ibu dan Anak Puji Astuti - Permadi, Abednego Cahya; Gunawan, Ibnu; Santoso, Leo Willyanto (Jurnal Infra, 2015)
The development of information technology has developed very rapidly following the needs of the times that require speed and accuracy in all aspects of life. Follow developments in terms of hardware, software, and in terms of human resources to operate. At this time almost all areas of life require information technology and human behavior are already accustomed to applying information technology in everyday life. With computers we can perform data processing and data storage. Can also perform data input, edit data, save it, and others. So that the data is managed more effectively and efficiently.Â With rapid advances in technology today, led to an idea or notion of the writer to try to computerize medical record recording in Maternal and Child Health Center Puji Astuti. The author tries to build an application that will help to facilitate the processing of medical data is more optimal and effective.The system will be made is